PENDIDIKAN KARAKTER PADA ANAK USIA DINI PERSPEKTIF PENDIDIKAN ISLAM - Muhammad Yusuf (Jurusan PGMI FTIK IAIN Metro Lampung, 2016)
This character education should be done from an early age, since an early age is the golden period of development (golden age) that its success largely determine the quality of a child in his adult life. all aspects of development in early childhood, indeed entered the stage or a very sensitive period. That is, if this stage is able to optimize the educational character of the child by providing a variety of stimulating productive, then the child character development in adulthood, will also take place productively. The current obstacle is modern education is dominated by the character of Western education offers a variety of educational concept-laden theories of psychology and philosophy of education. However, the concept that they offer hasn’t been able to give birth to a human being and a citizen who have cultural values and national character as well as religious or human-aware task and purpose of his life. Through educational methods, Islam offers a solution concept as the birth of a generation that is ready to sail and interpret life.